SOCIAL DISTANCING IN THE NEW NORMAL ERA IN TASAWWUF’S PERSPECTIVE: Study About The Al-Ghazali’s Opinion - Hijrah, Hijrah (Moderation | Journal of Islamic Studies Review, 2021)
Social distancingin the new normal era in tasawwuf‟s perspective is very important to be offered and very suitable to be publicated because of three reasons, first, the social interactive attitude in tasawwuf‟s perspective is relevant with the requipment 0f social interactive in New Normal era. Second, for strategy of interaction in new normal era is not only for the world importance only (health), but also it has a long and goal in the future to get the happiness in hereafter. Third, strategy of social interaction that get source from religion doctrin will be received faster and it is very essy to be done. This research is qualitative descriptive research. This kind of research is library research, that is a set of activities about the metode of collecting library data, reading and writing and processing research material. The important of socialdistancing in daily interactions in tasawuf‟s perspective because of two reasons; first, the creature disturb concentration of worship. Second, creature cause the reward of worship losing. At realm of social distancing strategy in tasawwuf‟s perspective clarify human in two part; First, layman, second,holyman who needed by many people. For layman, he may not in the crowds except possitve assemblage, such as praying together or activity to find money or livehood for life. Whereas the holyman in second criteria may not live alone and avoid from social activites. Keep the continuity of social distancing, there are three things that must be looked; first, make our selves busy with the positive things at home. Second, we always remember the dangerous of interaction in the crowds condition. Third, we minimalize our dependence to other people.